Life satisfaction among older adults in China: who gains more from community-based health services? - Jia, Cangcang; Zhang, Ling; Wang, Zhengyang; Li, Zhiguang (Frontiers in Public Health, 2025)
ObjectivesThis study investigates the effects of community-based health services on life satisfaction among older adults in China, examining three specific service types: health check-ups, health records, and health education programs.MethodsA cross-sectional quantitative study utilizing data from the China Longitudinal Aging Social Survey (CLASS) conducted in 2020. Ordinary Least Squares (OLS) regression models were employed for the benchmark analysis, with ordered logit and ordered probit models used for robustness verification. Propensity Score Matching (PSM) method with multiple algorithms was adopted to address potential selection bias and strengthen the basis for causal inference. Variable substitution and sample replacement methods were implemented for additional robustness tests. Heterogeneity analyses were conducted to examine differential effects across demographic subgroups.ResultsThe analysis included 11,292 older adults aged 60 and above. Health check-up services showed the highest utilization rate (29.93%), followed by health records (10.85%) and health education (7.03%). All three community-based health services showed significant positive associations with life satisfaction, with relationships that remained statistically significant after rigorous statistical adjustment for observable confounders. The positive effects remained consistent across different model specifications and robustness checks. Heterogeneity analyses revealed that female, rural, and chronically ill older adults experienced greater benefits from these services compared to their counterparts.ConclusionCommunity-based health services show strong positive associations with enhanced life satisfaction among older adults in China, with differential impacts across population subgroups. These findings provide evidence for expanding community-based health service coverage and developing targeted interventions for vulnerable older populations, particularly focusing on rural areas and individuals with chronic conditions to maximize program effectiveness.